Towards Sustainable Urbanization. Learning from What’s Out There - Alys Solly; Erblin Berisha; Giancarlo Cotella (Land, 2021)
The incremental recognition of the importance of land as a finite resource has led to the adoption and implementation of an increasing number of sustainable land use practices in European cities and regions. This paper reflects on these experiences, building on the evidence collected in the framework of the ESPON SUPER pan-European research project. In particular, the authors look at the project’s database, which includes 235 examples of sustainable urbanization interventions gathered from all around Europe. In doing so, they reflect on the outcomes of these interventions, focusing on both their scope and objectives and the types of instruments that were adopted in their implementation. The objective of this contribution is to critically analyze the rich set of practices collected throughout the project and to provide guidance for decision and policy makers aiming at promoting a more sustainable use of land. In this light, it suggests a number of recommendations and warnings, bearing in mind that no “right instruments” or “right targets” exist that could prove successful for all European cities and regions.